Age-related differences in flexibility in soccer players 8-19 years - Cejudo, A.; Robles-Palazón, F. J.; Ayala, F.; De Ste Croix, M.; Ortega-Toro, E.; Santonja-Medina, F.; Sainz de Baranda, P. (PeerJ, 2019)
Background: Muscle flexibility is a main component of health-related fitness and one of the basic components of fitness for the performance in some sports. Sport and health professionals require the flexibility profile of soccer to define quantitative aims in the training of flexibility. The aim of this study was to identify age-related differences in lower extremity flexibility in youth soccer players. Methods: Seventy-two young male soccer players (age: 13.0 ± 3.1 y; body mass: 50.5 ± 15.3 kg; stature 158.2 ± 16.8 cm; BMI: 19.6 ± 2.6 kg/m2) completed this study. Measures of eleven passive hip (hip extension (HE), hip adduction with hip flexed 90°(HAD-HF90°), hip flexion with knee flexed (HF-KF) and extended (HF-KE), hip abduction with hip neutral (HAB) and hip flexed 90°(HAB-HF90°), hip external (HER) and internal (HIR) rotation), knee (knee flexion (KF)) and ankle dorsiflexion (ankle dorsiflexion with knee flexed (ADF-KF) and extended (ADF-KE)) ranges of motion (ROM) were taken. Descriptive statistics were calculated for hip, knee and ankle ROM measured separately by leg (dominant and non-dominant) and age-group (U10, U12, U14, U16 and U19). The data was analysed using a one-way analysis of variance (ANOVA) to examine the interaction of 11 ROM in the different players` age-group. Results: Generally, U10 and/or U12 soccer players obtain the highest mean value in almost all ROM evaluated (U10: HAD-HF [39.6° ± 4.3°], ADF-KE [32.3° ± 4.1°], HER [63.5° ± 5.6°] and HAB-HF90°[64.1° ± 7.5°]; U12: HE [17.7° ± 6.2°], HAB [35.6° ± 3.0], HIR [60.8° ± 4.7°] and KF [133.8° ± 7.1°]). Nonetheless, significant differences between the players` age-groups are just found in HAD-HF90°(p = .042; ES = .136), HAB (p = .001; ES = .252), HIR (p = .001; ES = .251), HER (p < .001; ES = .321) and HAB-HF90°(p < .001; ES = .376) ROM, showing a progressive and irregular decrease in these ROM until the U19 team. Conclusion: The findings of this study reinforce the necessity of prescribing exercises aimed at improving HAD-HF90° ROM in U16, HAB ROM in U14, HIR ROM in U16 and U19, HER ROM in U12 and U19, and HAB-HF90° ROM in U16 and U19 players within everyday soccer training routines.